Slope Stability Analysis and Disposal Geometry Design Based on Saturation Level at PT. Prolindo Cipta Nusantara - Cahyono, Yudho Dwi Galih; Ode, Dandi Gusti; Saputro, Eko Budi (Universitas Pembangunan Nasional (UPN), 2024)
Prolindo Cipta Nusantara Ltd. location is on Sebamba Baru Village, Sungai Lobam. Tanah Bambu, South Kalimantan and it had land permitted around 350 hectares. This company is engaged in the coal mining business. In the beginning of mining process is stripping the overburden and disposal is required to accommodate overburden materials from pit. The method used to determine and analyze the problems in this study was boundary equilibrium method assisted by Side 6.0 software to make disposal slope modeling and analyze disposal slope safety factor. The result was making recommendation for safe and stable disposal to accommodate overburden materials from pit. The recommended disposal slope was disposal slope design in natural condition with a single slope geometry, 10 meters for the height, and 35 degrees for a slope angle. The overall slope geometry had a height of 90 meters and a slope angle of 10 degrees and it produced a safety factor value of 1,302 and the disposal slope design in a saturated condition with a single slope geometry was 10 meters high and 30 degrees for a slope angle. The height of overall slope geometry was 84 meters and tilt angle was 9 degrees and it produced a safety factor value of 1.257.